Central banks' voting records, and future policy - Roman Horváth; Kateřina Šmídková; Jan Zápal (Institut für Ost- und Südosteuropaforschung (IOS), 2012)
We assess whether the voting records of central bank boards are informative about future monetary policy using data on five inflation targeting countries (the Czech Republic, Hungary, Poland, Sweden and the United Kingdom). We find that in all countries the voting records, namely the difference between the average voted-for and actually implemented policy rate, signal future monetary policy, making a case for publishing the records. This result holds even if we control for the financial market expectations; include the voting records from the period covering the current global financial crisis and examine the differences in timing and style of the voting record announcements.
urn:nbn:de:101:1-201207106459
Keywords: D78; E52; E58; 330; monetary policy; voting record; transparency; collective decision-making; Geldpolitik; Zentralbank; Gruppenentscheidung; Prognoseverfahren; Inflationssteuerung; Tschechische Republik; Ungarn; Polen; Schweden; Großbritannien